Canadian Helicobacter Study Group Consensus Conference on the Approach to Helicobacter Pylori Infection in Children and Adolescents. (1st September 1999) - Sherman, P; Hassall, E; Hunt, RH; Fallone, CA; Veldhuyzen van Zanten, S; Thomson, ABR; Canadian Helicobacter Study Group,
Abstract : Gastric infection with Helicobacter pylori is common in both children and adults, but children are considerably less susceptible to peptic ulcers and other pathological sequelae. As a result, the risk to benefit ratio of diagnostic studies and therapeutic regimens for H pylori in adults are likely different from those in paediatric populations. These guidelines for the management of paediatric H pylori infection, developed by the Canadian Helicobacter Study Group, are designed to identify when the diagnosis and treatment of H pylori may improve patient care. Given the low prevalence of this infection in Canada, it is important to recognize that indiscriminate testing and treatment programs in children are not recommended, and indeed may threaten the optimal care of children. Diagnostic tests should be employed judiciously and be reserved for children who are most likely to derive measurable benefit, such as those likely to have peptic ulcer disease. At this time a test and treat strategy in children cannot be considered prudent, evidence based or cost effective. It is appropriate to limit diagnosis and treatment to children and adolescents in whom H pylori has been identified during endoscopic investigation.